IMPROVING THE QUALITY OF HANDICRAFT PRODUCTS OF ENDEK WEAVING FROM DESIGN DIMENSIONS AND PRODUCTION PROCESSES TO SUPPORT THE CONSUMER PURCHASE DECISIONS AND THE EFFECT ON THE EXISTENCE OF RURAL CREATIVE INDUSTRIES - Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2017)
Abstract- Background of this research is to know: (1) design pattern and production process developed by weaving SMEs in Gelgel and Sampalan Village; (2) the carrying capacity of product quality to the consumer's decision to conduct buying activity; (3) The existence of weaving SMEs with strategies in production and management. The effectiveness of the development of endek endek handicraft business should deserve important attention to be productive so that it succeeds in increasing production capacity and business management. Methods and design of research in the form of integrated simulation system modeling design, The influence of all forms of potential arrangement of hand crafted endek belt weaving with environmentally friendly way. The result of the research, design pattern and production process developed by weaving SMEs in Gelgel and Sampalan Village continue to be developed and successfully applied some computer design innovation which offer different style with other craftsman including production process always have monitoring by weaving owner to keep product quality starting from the beginning up to the finishing stage. The high market demand is supported from one of them due to the quality of the products produced by weaving in Gelgel and Sampalan region. Strategies in the field of production and management have a significant influence on the increase in activity penjulan and existence of a company that became known by consumers of endek cloth lovers.Keywords: Endek, Gelgel, quality, management, improvement, craftsman, production, ikat, Sampalan.